The ω6-fatty acid, arachidonic acid, regulates the conversion of white to brite adipocyte through a prostaglandin/calcium mediated pathway - Didier F. Pisani; Rayane A. Ghandour; Guillaume E. Beranger; Pauline Le Faouder; Jean-Claude Chambard; Maude Giroud; Alexandros Vegiopoulos; Mansour Djedaini; Justine Bertrand-Michel; Michel Tauc; Stephan Herzig; Dominique Langin; et al. (Elsevier, 2014)
Objective: Brite adipocytes are inducible energy-dissipating cells expressing UCP1 which appear within white adipose tissue of healthy adult individuals. Recruitment of these cells represents a potential strategy to fight obesity and associated diseases. Methods/Results: Using human Multipotent Adipose-Derived Stem cells, able to convert into brite adipocytes, we show that arachidonic acid strongly inhibits brite adipocyte formation via a cyclooxygenase pathway leading to secretion of PGE2 and PGF2α. Both prostaglandins induce an oscillatory Ca++ signaling coupled to ERK pathway and trigger a decrease in UCP1 expression and in oxygen consumption without altering mitochondriogenesis. In mice fed a standard diet supplemented with ω6 arachidonic acid, PGF2α and PGE2 amounts are increased in subcutaneous white adipose tissue and associated with a decrease in the recruitment of brite adipocytes. Conclusion: Our results suggest that dietary excess of ω6 polyunsaturated fatty acids present in Western diets, may also favor obesity by preventing the "browning" process to take place.